Knowledge, Attitude, and Practices of Antibiotics and Antibiotic Resistance Among Chinese Pharmacy Customers: A Multicenter Survey Study - Pengchao Li; Khezar Hayat; Li Shi; Krizzia Lambojon; Amna Saeed; Muhammad Majid Aziz; Tao Liu; Shiyu Ji; Yilin Gong; Zhitong Feng; Minghuan Jiang; Wenjing Ji; et al. (Antibiotics, 2020)
Background: Resistance to antibiotics is one of the major global health challenges. An adequate understanding of the public regarding rational antibiotic use is a prerequisite to limit progression in antibiotic resistance. This study aimed to investigate the knowledge, attitude, and practices (KAP) of antibiotics and antibiotic resistance among customers visiting community pharmacies. Methods: This study was undertaken in three capital cities in China during March 2019 and July 2019 by using a questionnaire of 28 items. The questionnaire had four parts, including sociodemographic characteristics, KAP about antibiotics, and antibiotic resistance. A systematic random sampling approach was used to recruit the participants. Kruskal–Wallis and Mann–Whitney tests were carried out for data analysis. Results: The response rate was 66.7% (1800/2700). Out of the total, only 9.7% of the customers had good knowledge about antibiotics. Nearly half of the participants were unable to differentiate between antibiotics, and anti-inflammatory drugs (n = 820, 45.6%, Median = 2, IQR = 1). Most of the customers were of the view that the use of over the counter antibiotics in pregnant women is unsafe (n = 1307, 72.6%, Median = 2, IQR = 0). Almost half of the participants disagreed that costly antibiotics are more effective and have fewer side effects (n = 897, 49.9%, Median = 3, IQR = 1). Only 22.3% of participants said that they always finish the course of antibiotic treatment (n = 401, 22.3%, Median = 3, IQR = 1). Conclusion: The knowledge of Chinese pharmacy consumers was inadequate, and a lack of good attitudes and practices in certain aspects of antibiotic use was observed. Educational interventions are needed to increase public knowledge of antibiotics.